Organization and regional distribution of centers for the management of children and adolescents with diabetes in Italy. Issue 1 (December 2015) - Giorgetti, Chiara; Ferrito, Lucia; Zallocco, Federica; Iannilli, Antonio; Cherubini, Valentino
Abstract Background The incidence of type 1 diabetes in childhood is increasing by 3 % per year, placing growing demands on healthcare professionals and medical expenditures. Aim of this study wars to assess the organization of care to children with diabetes in Italy. Methods During 2012 a structured questionnaire was sent to all of the members of Italian Society of Paediatric Endocrinology and Diabetology (ISPED). Questions examined organizational structure of Centers, personnel dedicated to the care of children with diabetes, number of subjects followed, local legal legislation supporting centres. Results A total of 68 centers taking care to 15, 563 children and adolescents with diabetes under 18 years of age were identified with a prevalence of 1.4 per 1, 000 people. A wide variation in the organizational background was also reported. Fourty-four centers were organized as outpatient departments, 17 as simple units, 5 as complex units and 2 as simple departmental structures. Most centers had a multidisciplinary team. Ten out of twenty Italian regions had introduced supportive regional legislation, but it was fully applied only in six of them. Conclusion Great differences between regions were found in organizational structures, staffing levels and supportive legislation. The national legislation on diabetes was broadly implemented throughout the country regions. Further efforts are needed to improve standards and consistency of pediatric diabetes care in Italy.